synthesis and characterization of copper nanoparticle - chitosan - Thien, Do Truong; Tuyen, Nguyen Van; Y Nhi, Tran Thi (Vietnam Journal of Chemistry, 2014)
Copper nanoparticles were synthesized in the presence of chitosan via reduction of Cu(NO3)2with sodium borohydride with the ratio of 4 ml 2.0 mg/ml chitosan : 2ml Cu(NO3)210 mM : 1 ml NaBH40.1 M in aqueous solution. Chitosan molecules absorbing on the surface of prepared copper nanoparticles formed the corresponding copper nanoparticle-chitosan. The resulting copper nanoparticles were characterized by transmission electron microscopy (TEM) and UV- visible (UV-VIS) spectroscopy. It was found that an absorbance band at 805 nm was observed in UV-VIS spectra and the copper nanoparticles were found to be spherical with a narrow size distribution, the average diameter was about 3 nm.